European society of neurogastroenterology and motility guidelines on functional constipation in adults. Issue 2 (22nd November 2019) - Serra, Jordi; Pohl, Daniel; Azpiroz, Fernando; Chiarioni, Giuseppe; Ducrotté, Philippe; Gourcerol, Guillaume; Hungin, A. Pali S.; Layer, Peter; Mendive, Juan‐Manuel; Pfeifer, Johann; Rogler, Gerhard; Scott, S. Mark; et al.
Abstract: Introduction: Chronic constipation is a common disorder with a reported prevalence ranging from 3% to 27% in the general population. Several management strategies, including diagnostic tests, empiric treatments, and specific treatments, have been developed. Our aim was to develop European guidelines for the clinical management of constipation. Design: After a thorough review of the literature by experts in relevant fields, including gastroenterologists, surgeons, general practitioners, radiologists, and experts in gastrointestinal motility testing from various European countries, a Delphi consensus process was used to produce statements and practical algorithms for the management of chronic constipation. Key Results: Seventy‐three final statements were agreed upon after the Delphi process. The level of evidence for most statements was low or very low. A high level of evidence was agreed only for anorectal manometry as a comprehensive evaluation of anorectal function and for treatment with osmotic laxatives, especially polyethylene glycol, the prokinetic drug prucalopride, secretagogues, such as linaclotide and lubiprostone and PAMORAs for the treatment of opioid‐induced constipation. However, the level of agreement between the authors was good for most statements (80% or more of the authors). The greatest disagreement was related to the surgical management of constipation. Conclusions and Inferences: European guidelines on chronic constipation, with recommendations and algorithms, were developed by experts. Despite the high level of agreement between the different experts, the level of scientific evidence for most recommendations was low, highlighting the need for future research to increase the evidence and improve treatment outcomes in these patients. Abstract : We produced a guideline for management of functional constipation that provides evidence‐based practical algorithms for diagnosis and stepwise treatment of constipation in adults. Implementation of the guideline should improve and harmonize management of constipation across different countries.